Determinants of obesity indices among primary healthcare workers in Perak, Malaysia - Low, Pei Kit (2019)
Overweight and obesity have been emerging as one of the most preventable nutritional problems worldwide. The most commonly used obesity indices to classify obesity are body mass index (BMI) and waist circumference, yet it has some drawbacks which affecting their reliability. Bioelectrical impedance analysis (BIA) has been suggested as a better index in determining obesity-related health risk by direct assessing the body fat mass. A cross-sectional study was conducted at 12 selected health clinics around Perak to determine the prevalence of obesity and investigate the determinants of obesity indices among the primary healthcare workers. Data were collected using self-administered questionnaire consisting seven sections include socio-demographic characteristics, physical activity, dietary intakes, sleep quality, psychological distress, smoking habits, and anthropometric measurements (BMI, waist circumference and body fat percentage). Findings showed that 49.9% of the primary healthcare workers were overweight and obese, 51.0% have abdominal obesity and 79.7% have high body fat percentage. Combined indices showed that 44.5% of them fell into the abnormal categories for all three indices. There were 45.6% of the primary healthcare workers categorised as physically inactive and spent a median of five hours daily in sedentary behaviours. More than half of them do not have enough calorie and micronutrients intakes. On the contrary, most of them showed good indication in psychological distress and were good sleepers. Only 4.6% primary healthcare workers categorised as ever smokers but more than 50% were passive smokers. Bivariate analysis showed that older age, good self-reported health status and implausible dietary intakes were significantly associated with all the three obesity indices. Professionals have significantly lower BMI whereas higher educational level have both lower BMI and waist circumference. Primary healthcare workers with abdominal obesity and high body fat percentage tend to have micronutrients deficiencies (calcium, zinc, vitamin E and vitamin B12). Lastly, good sleep quality and non-smokers were significantly associated with high body fat percentage. Logistic regression analysis showed that plausibility of dietary intakes made the strongest significant contribution to all three obesity indices. Self-reported health status was found to be another predictors for both waist circumference and body fat percentage. In addition, vitamin E and zinc deficiency, good sleep quality and nonsmokers were linked to high body fat percentage. In conclusion, all the three obesity indices showed that obesity were prevalent among the primary healthcare workers in Perak and plausibility of dietary intakes made the strongest contribution as predictors for obesity. It is essential to increase the awareness and behavioural change among the primary healthcare workers. Practical approach such as continuous education to promote healthy lifestyle should be carried out.